A CASE STUDY OF ESG IMPLEMETION OF SMALL AND MEDIUM BUSINESS- EXAMPLE BY SHERIFF TEA EGG - Li Hua Shih; Hui Chun Chiu; Te Tsai Lu (Graduate Program of Universitas Tarumanagara, 2025)
This study examines the case company of “Sheriff Tea Egg” to explore how traditional small and medium-sized enterprises (SMEs) in Taiwan implement Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) practices, aligning their efforts with both the Global Reporting Initiative (GRI) standards and the United Nations Sustainable Development Goals (SDGs). Emphasizing the challenges and strategic adaptation of SMEs under resource limitations, the research offers practical recommendations for effective ESG integration.Using a qualitative case study methodology, the research collected comprehensive data through secondary sources, in-depth interviews, and expert consultations, focusing on Sheriff Tea Egg’s sustainable initiatives across environmental, social, and governance dimensions. Guided by GRI topic-specific standards, stage-appropriate indicators were developed, and interviews with senior management were conducted to analyze the company’s ESG actions and outcomes.The study identifies a three-phase sustainability transformation at Sheriff Tea Egg. In the first phase, the company centered on charitable giving–regularly donating profits and creating “charity bamboo tubes”—building its image of social accountability. The second phase involved integrating employee welfare, employment for individuals with disabilities, community co-creation, and sustainable packaging to strengthen social links both internally and externally. In the third phase, Sheriff Tea Egg introduced carbon footprint certification, sourced eggs that adhere to animal welfare standards, designed eco-friendly packaging, and expanded its sustainable supply chain—culminating in a systematic governance framework fully aligned with ESG criteria and SDG objectives. Although a small enterprise, Sheriff Tea Egg overcame its resource constraints through strategic CSR, collaboration with local stakeholders, and inclusive employment, achieving multifaceted sustainable governance. The company’s phased, goal-driven ESG progression demonstrates that even SMEs with limited scale can create shared value for both business and society. This case offers valuable lessons for other SMEs. Furthermore, this study contributes to the academic field by addressing the lack of empirical ESG research among Taiwanese SMEs and offers actionable recommendations, such as establishing a simplified GRI implementation framework, leveraging local resources for value co-creation, adopting phased carbon management and sustainable packaging strategies, and designing products with social innovation at their core.